Perancangan Sistem Informasi Pelayanan Klinik Alidza Kota Padang Berbasis Web - Riki Iskandar; Dinul Akhiyar (Universitas Putra Indonesia YPTK Padang, 2020)
Research has been carried out at the Padang City Alidza Clinic, where the problem which is the basis of this writing is the savings and loan data processing information system. Through the process of direct observation of spaciousness we have found the weaknesses of the existing system. Although not as a whole, it is more directed to a specific problem, but is expected to make a meaningful contribution to system users. The author designed a clinical service information system that is able to tackle Alidza Padang Padang clinical problems and can produce information on time and the results of that information can be more accurate. In designing this new system, the programming language PHP, UML and MySQL database are used. With this clinical information system the process of recording service data is more efficient and effective because it uses a computerizedsystem.